2011
DOI: 10.1134/s0006297911080104
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated protein kinases mediate the production of B-cell lymphoma 2 protein by Mycobacterium tuberculosis in Monocytes

Abstract: Changes in the levels of antiapoptotic protein B-cell lymphoma 2 (Bcl-2) protein has been reported in murine and human tuberculosis. We investigated the role of mitogen-activated protein kinase pathways in the production of Bcl-2 protein in THP-1 human monocytes infected with Mycobacterium tuberculosis H37Rv and H37Ra. Analysis of phosphorylation profiles of mitogen-activated protein kinase kinase-1, extracellular-signal regulated kinase 1/2, mitogen-activated protein kinase kinase 3/6, and p38 mitogen-activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…The involvement of the Bcl-2 family of proteins in preventing or inducing host-cell death has been explored for bacterial pathogens like Mycobacterium tuberculosis where infection upregulates Bcl-2 in mouse macrophages and THP-1 cells through the mitogen-activated protein kinase (MAPK) pathway (11). Another bacterial pathogen M. leprae , downregulates pro-apoptotic Bcl-2 family members Bad and Bak and upregulates the antiapoptotic Mcl-1 protein to prevent host-cell apoptosis (12).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of the Bcl-2 family of proteins in preventing or inducing host-cell death has been explored for bacterial pathogens like Mycobacterium tuberculosis where infection upregulates Bcl-2 in mouse macrophages and THP-1 cells through the mitogen-activated protein kinase (MAPK) pathway (11). Another bacterial pathogen M. leprae , downregulates pro-apoptotic Bcl-2 family members Bad and Bak and upregulates the antiapoptotic Mcl-1 protein to prevent host-cell apoptosis (12).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that only virulent M. tuberculosis H37Rv induced expression of the Mcl-1 protein, an antiapoptotic member of the Bcl-2 family, after in vitro infection of human THP-1 cells [49]. In parallel, a weaker induction of TNFα expression was observed in human and mouse cells following in vitro infection with virulent than non-virulent strains [50][51][52]. Following in vivo infection of zebrafish (Danio rerio) juveniles with M. marinum, mycobacteria spread in their organisms due to the death of some granuloma macrophages and the release of mycobacteria into the extracellular environment, where they were later phagocyted by uninfected macrophages [28,53].…”
Section: Introductionmentioning
confidence: 80%
“…Natarajan and Sujatha observed a twofold increase in Bcl-2 levels as early as 24 h after in vitro infection of ТНР-1 monocyte-like cells with the virulent strain H37Rv of M. tuberculosis [52]. By contrast, blood mononuclear cells and human ТНР-1 cells infected in vitro with attenuated ВСG mycobacteria or non-virulent M. tuberculosis strain H37Rа had a considerable reduction in Bcl-2 protein after 24 h following infection [52,75]. We did not observe activation of Bcl-2 synthesis at hours 4-120 of analysis in the macrophages from bone barrow cell cultures and peritoneal exudates infected with BCG mycobacteria in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations